Study on overburden failure characteristics and ground pressure behavior in shallow coal seam mining underneath the gully - Zhang, Jie; Wang, Li; Yang, Tao; Gao, Shoushi; He, Yifeng; Wu, Jianjun (Frontiers in Earth Science, 2024)
This work investigated overburden failure characteristics and ground pressure behavior in shallow coal seam mining underneath the gully by taking the 135201 working face of Shaliang Coal Mine in Shenfu Mining Area as the engineering background.The ground pressure and overburden failure characteristics at the working face for shallow coal seam mining underneath the gully were studied by means of physical similarity simulation test, theoretical analysis, and field measurement. The results revealed that the ground pressure at the working face in the uphill section was stronger than these in the gully bottom and downhill sections, and the weighting interval in the uphill section was the smallest. Based on the monitored ground pressure law in the field and the overburden failure characteristics of shallow coal seam underneath the gully obtained by using physical similarity simulation test, a mechanical analysis model for the failure structure of key stratum in the uphill section was established, and the calculation formula for weighting interval in the uphill section was derived. Also, the relationship among the caving interval and the thickness of key stratum in the uphill section as well as the gully slope was analyzed.The on-site measurement results were in good agreement with the theoretical results. Furthermore, the prediction method for ground pressure , along with the hazard prevention and control measures for shallow coal seam mining underneath the gully, were proposed.